Geochemical Comparison of two Tervola Volcanite Deposits as Plausible Stone Tool Material Sources in Kemijoki - Eranti, Olli (Helsingin yliopisto, 2020)
Geochemistry of stone tools and sources remains largely unknown in Finnish archaeology, but the potential is promising. Most formal Finnish stone tools beside quartz are made from ground metamorphic stone, which often has a specific source of collection. Geochemistry can reveal compositional and trace element links between the sources and tools found in various Stone Age settlement sites. Discoveries about technological properties of the stone types can be a helpful comparison, since many geochemical methods can produce data that has inconsistencies. In this thesis both geochemical and technological aspects of two lithic material sources are examined. Samples were collected from two lithic material sources: Rakkaviita and Rieskapaikka in Tervola, Southern Lapland. The 62 collected samples were measured with a Bruker S1 Titan portable x-ray fluorescence device as a preliminary method. Three samples from Rakkaviita and two samples from Rieskapaikka were chosen for the primary method, which was the PANalytical Axios mAX 4 kW, Wavelength Dispersive X-Ray fluorescence spectrometer in the Department of Geosciences in the University of Helsinki. The data from these measurements is evaluated and plotted to reveal geochemical properties of the stone. In this study, the properties of these stone materials are documented for the first time, so it can also be considered as a mapping study. The measurements revealed differentiation between methods, especially on the SiO2 percentages. The WD-XRF measurements are done without sample specific calibration, which obscures the quantitative proportions of some elements. The content of the stone revealed various components in different proportions. The result of major components was a coarsely qualitative definition of stone from both sources, which can be used in further material studies of stone tools. The trace element comparison between yttrium (Y) and strontium (Sr) revealed clear similarity between sources, excluding one sample that had significantly different tool production ...